Development of a social sustainability model in industrial building system - Taherkhani, Roohollah (2013)
Industrialization of building systems is a key country-level strategy toward sustainable development. Due to sustainability international concerns, the concept of Industrial Building System (IBS) has received significant attention toward sustainable construction in Malaysia. Therefore, the transformation from traditional construction methods to the sustainable IBS methods is crucial for the country. In this regard, a control mechanism of building systems is necessary to monitor the economic, environmental and social aspects of sustainability. The previous researches indicate the social dimension as the fundamental part of sustainability has received far less attention. To date, despite growing researches on IBS and sustainability, there is no social sustainable framework and model in IBS at the country level. Therefore, this research proposes to develop a social sustainability model in IBS and advances the concept of social sustainability by presenting an applicable framework which is approved through Confirmatory Factor Analysis (CFA). Based on this framework the Analytic Hierarchy Process (AHP) was implemented to determine the most suitable social sustainability model in building systems. In compare with the social sustainability factors ranking obtained from AHP model, variety of ranking methods has been investigated to assess the priority of IBS social sustainability factors. Then, a hybrid model, using AHP and Neural Network (NN) methods, is developed to assess IBS Social Sustainability Power Ratio (SSPR). The result from this hybrid model shows SSPR is 0.7212 which is categorized in acceptable level. Nevertheless IBS as a primary step towards sustainable construction must perform careful planning to upgrade its social sustainability factors. The result suggests that development of IBS need to be more concentrated toward social sustainability. The presented social sustainability hybrid model can use as an assessment and a guideline within IBS supply chain players.